Link of sorafenib resistance with the tumor microenvironment in hepatocellular carcinoma: Mechanistic insights - Tian, Xinchen; Yan, Tinghao; Liu, Fen; Liu, Qingbin; Zhao, Jing; Xiong, Huabao; Jiang, Shulong (Frontiers in Pharmacology, 2022)
Sorafenib, a multi-kinase inhibitor with antiangiogenic, antiproliferative, and proapoptotic properties, is the first-line treatment for patients with late-stage hepatocellular carcinoma (HCC). However, the therapeutic effect remains limited due to sorafenib resistance. Only about 30% of HCC patients respond well to the treatment, and the resistance almost inevitably happens within six months. Thus, it is critical to elucidate the underlying mechanisms and identify effective approaches to improve the therapeutic outcome. According to recent studies, tumor microenvironment (TME) and immune escape play critical roles in tumor occurrence, metastasis and anti-cancer drug resistance. The relevant mechanisms were focusing on hypoxia, tumor-associated immune-suppressive cells, and immunosuppressive molecules. In this review, we focus on sorafenib resistance and its relationship with liver cancer immune microenvironment, highlighting the importance of breaking sorafenib resistance in HCC.